2005
DOI: 10.1258/0023677054307033
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantitative assessment of catheter patency in rats

Abstract: Formation of fibrin sleeves around catheter tips is a central factor in catheter failure during chronic implantation, and such tissue growth can occur despite administration of anticoagulants. We developed a novel method for monitoring catheter patency. This method recognizes the progressive nature of catheter occlusion, and tracks this process over time through measurement of changes in catheter resistance to a standardized 1 mL bolus infusion from a pressurized reservoir. Two indirect measures of catheter pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
0
27
0
1
Order By: Relevance
“…Unlike PK and MK-4, accurate measurement of MD in biological fluids by physicochemical means is difficult because of its high volatility. Thus, we developed a novel method for the measurement of MD (putative MD-d 7 ) using rhUBIAD1 as a source of converting enzyme and deuterium-labeled geranylgeranyl pyrophosphate (GGPP-d 5 ) as a source of the side chain in the final product (putative MK-4-d 12 ). In this method, MD-d 7 in the lymph and serum was converted to MK-4-d 12 , which was quantitatively detected by atmospheric pressure chemical ionization-liquid chromatography-tandem mass spectrometry (APCI-LC-MS/MS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike PK and MK-4, accurate measurement of MD in biological fluids by physicochemical means is difficult because of its high volatility. Thus, we developed a novel method for the measurement of MD (putative MD-d 7 ) using rhUBIAD1 as a source of converting enzyme and deuterium-labeled geranylgeranyl pyrophosphate (GGPP-d 5 ) as a source of the side chain in the final product (putative MK-4-d 12 ). In this method, MD-d 7 in the lymph and serum was converted to MK-4-d 12 , which was quantitatively detected by atmospheric pressure chemical ionization-liquid chromatography-tandem mass spectrometry (APCI-LC-MS/MS).…”
mentioning
confidence: 99%
“…(9). PK-d 7 , MK-4-d 7 , MK-4-d 12 , their respective epoxides, and GGPP-d 5 were also synthesized in our laboratory as reported previously (10,11). The synthesis and unambiguous physicochemical assignments of these deuteriumlabeled vitamin K compounds have been described elsewhere (10,11).…”
mentioning
confidence: 99%
“…A study carried out in rats by (Yang et al, 2005) assessed catheter patency for up to 63 days using two routes of infusion: jugular vein and femoral vein in combination with two different infusion fluids, heparinised saline or heparinised saline containing dexamethasone and several types of catheter tubing. The authors found that the combination of heparinised saline containing dexamethasone, infused via the femoral vein and the use of silastic tubing resulted in a useful infusion over 9 weeks (Yang et al, 2005). It is conceivable that their methods could have been combined with our vEEG/infusion system to further enhance the success of chronic infusions.…”
Section: Discussionmentioning
confidence: 99%
“…All animal experiments in this study were performed with the approval of the Animal Care and Use Committee of Saint Louis University School of Medicine, and in accordance with the National Institutes of Health Guidelines for ethical animal treatment. Three days prior to the induction of sepsis, a femoral vein catheter was inserted into the animal (25) to serve as an access port for intravenous injection of ODNs and saline. Sepsis was induced by cecal ligation and puncture (CLP) as described by Wichterman et al (26) except that buprenorphine HCl, 0.5 mL/kg subcutaneous, was administered for added postoperative pain control three times at 12-hr intervals.…”
Section: Determinations Of Clinical Efficacies Of Antisense Odns In Imentioning
confidence: 99%